Comparison of Postoperative Quality of Recovery and Pain Relief with Preoperative Single-Dose Dexamethasone and Lignocaine after Laparoscopic Cholecystectomy - Surender (Anesth Essays Res, 2018)
AIM: To compare the role of single intravenous (IV) bolus of lignocaine and dexamethasone on pain score and quality of recovery score (QoR40) after laparoscopic cholecystectomy. SETTING AND DESIGN: The study was conducted at the postoperative recovery area, This was a double-blind randomized controlled study. MATERIALS AND METHODS: Seventy patients 18–60 years of age, American Society of Anesthesiologists physical status Class I and II, who underwent elective laparoscopic cholecystectomy, were enrolled in this study after approval from the Institutional Ethics Committee. Patients were randomly allocated to two groups. Group 1 received: 2 mg/kg lignocaine diluted to 10 ml with normal saline, and Group 2 received 0.1 mg/kg IV dexamethasone diluted to 10 ml with normal saline. Global QoR-40 is a 40-item questionnaire that provides a global score and subscores across five dimensions: psychological support, comfort, independence, pain, and emotions. It was assessed on a preoperative day as baseline to assess patient's basic quality of life and at 24 h postoperative. Visual analog scale (VAS) static and dynamic, total analgesic consumption in a day, nausea and vomiting, and antiemetic per day were assessed. STATISTICAL ANALYSIS USED: Student's t-test, Chi-square test, Fisher's exact, Levene's test were used for statistical analysis. RESULTS: Dexamethasone group had higher Global QoR-40 than lignocaine group 187.94 versus 182.85. Among dimensions of QoR-40, dexamethasone had statistically better physical comfort, physical independence, and pain relief as compared to lignocaine. Dexamethasone group had lower VAS compared to lignocaine group. Similarly, there was less fentanyl consumption in dexamethasone group (364.08 ± 127.31) in the postoperative period when compared to the lignocaine group (412.31 ± 147.8). CONCLUSIONS: Preoperative administration of a single dose of dexamethasone enhanced QoR after laparoscopic cholecystectomy as compared to lignocaine bolus dose.